2021
DOI: 10.21203/rs.3.rs-157718/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synovial fluid IL-1β appears useful for the diagnosis of chronic periprosthetic joint infection

Abstract: Purpose The purpose of this study was to investigate the role of synovial fluid interleukin (IL)-1β in diagnosing chronic periprosthetic joint infection (PJI) and to identify the optimal threshold of synovial fluid IL-1β for differentiating chronic PJI from aseptic failure after knee and hip arthroplasties.Methods Between January 2019 and December 2019, we prospectively included patients scheduled to have a revision surgery for chronic PJI or aseptic failure after total joint arthroplasty. Then synovial I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1, and the QUADAS‐2 score criteria revealed that most of the extracted studies had high risks. Excluding brand new markers that only appeared recently and have limited data, 129 records reported diagnostic information of serum markers (serum CRP, ESR, procalcitonin, IL‐6, D‐Dimer, WBC, platelet count [PLT], neutrophil to lymphocyte ratio [NLR], monocyte to lymphocyte ratio [MLR], platelet to lymphocyte ratio [PLR], platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), 9–11,24–149 114 studies reported synovial markers (synovial WBC, PMN%, IL‐6, IL‐1β, CRP, TNF‐α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral‐flow based α‐defensin test),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, and the QUADAS‐2 score criteria revealed that most of the extracted studies had high risks. Excluding brand new markers that only appeared recently and have limited data, 129 records reported diagnostic information of serum markers (serum CRP, ESR, procalcitonin, IL‐6, D‐Dimer, WBC, platelet count [PLT], neutrophil to lymphocyte ratio [NLR], monocyte to lymphocyte ratio [MLR], platelet to lymphocyte ratio [PLR], platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), 9–11,24–149 114 studies reported synovial markers (synovial WBC, PMN%, IL‐6, IL‐1β, CRP, TNF‐α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral‐flow based α‐defensin test),…”
Section: Resultsmentioning
confidence: 99%
“…Final analysis was performed on 215 articles with six additional studies searched manually, as shown in platelet to mean platelet volume ratio [PVR], FDP [fibrin degradation product] and Fibrinogen), [9][10][11] 114 studies reported synovial markers (synovial WBC, PMN%, IL-6, IL-1β, CRP, TNF-α, Calprotectin, and leucocyte esterase [LE] and laboratory or lateral-flow based α-defensin test), 10,29,31,34,36,43,49,51,52,58,59,61,62,64,65,[72][73][74]76,77,[79][80][81][84][85][86][87][88]90,95,97,99,117,118,122,124,125,127,129,132,[135][136][137][138]142,1...…”
Section: Study Selectionmentioning
confidence: 99%
“…A number of specific biomarkers showed promise in the diagnosis of PJI, including synovial soluble tumor necrosis factor receptor 2 (sTNF-R2) 33 , synovial fluid interleukin-1 beta (IL-1β) (especially in combination with the polymorphonuclear [PMN] percentage) 34 , and calprotectin (of note, calprotectin did not reliably differentiate PJI from rheumatoid arthritis in this study) 35 . In 1 study, a calprotectin point-of-care test showed high sensitivity and specificity (>95%) in the diagnosis of PJI after TKA 36 .…”
Section: Diagnosismentioning
confidence: 86%
“…16,17,20 In recent research performed by Ivy et al, 18 the diagnostic value of synovial α defensin in PJI was not superior to that of synovial white blood cell (WBC) count and polymorphonuclear neutrophil percentage (PMN%), but its test costs were higher than synovial WBC and PMN% test. There are other synovial biomarkers, including interleukin (IL)-1β, IL-6, cysteine-rich with EGF-like domains 2 and calprotectin, etc, 15,[21][22][23][24][25] but whether these really have a role in PJI diagnosis has not yet been established, as the sensitivities and specificities reported by previous studies are different. 15,21,22,25 Therefore, it is urgent to develop a novel biomarker to diagnose PJI precisely.…”
Section: Introductionmentioning
confidence: 99%